DEVELOPMENT AND EXPERIMENTAL CHARACTERIZATION OF AN IOT-CONTROLLED RGB LED LIGHTING SYSTEM FOR HYDROPONIC APPLICATIONS - S Worsoongnern; Witoon Yindeesuk; S Kamoldilok; K Srinuanjan; Pichet Limsuwan (Ukrainian Journal of Physical Optics, 2026)
This study presents the development of an Internet of Things-based RGB LED lighting system for precise, flexible light control in hydroponic plants.The system consists of 480 high-power RGB LEDs controlled by an ESP8266 microcontroller, enabling real-time adjustment of light intensity, photoperiod, and color ratios via a smartphone.Pulse-width modulation duty-cycle modulation enables the generation of white light suitable for different stages of plant growth.Experimental results show a linear correlation between illuminance and duty cycle for all color channels.Spectral analysis confirms stable emission within the photosynthetically active radiation range (400-700 nm), with the spectral composition remaining unchanged even when brightness is reduced (dimming).The system demonstrates high control accuracy and adaptability for regulating plant growth lighting, particularly for leafy vegetables such as lettuce.
Keywords: Impact of Light on Environment and Health; Technology and Education Systems; Embedded Systems and FPGA Design